2019
DOI: 10.30918/ajer.73.19.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characteristics of oleophilic gel polymer for oil spills cleanup

Abstract: This work studies the synthesis, characterization and evaluation of oleophilic gel based on butyl acrylate polymer (BA) to be used in oil spill removing applications. Poly(n-butyl acrylate) was synthesized by solution polymerization and the effect of different factors including polymerization time, initiator concentration, crosslinker concentration, monomer concentration and polymerization temperature on the % yield of butyl acrylate were studied to determine the optimal polymerization conditions. The thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…10 A variety of lignocellulosic biowastes have been used for oil spill removal, e.g., Ali et al reported the synthesis of oleophilic gels from n-butyl acrylate for oil spill cleanup. 11 Gum tragacanth, a natural polysaccharide, was grafted with acrylic acid and methylmethacrylate by Saruchi et al for oil spill remediation. 12 He et al proposed the utilization of aerogels derived from carboxymethylated chitosan which showed remarkable oil adsorption capacities along with excellent regeneration ability.…”
Section: Introductionmentioning
confidence: 99%
“…10 A variety of lignocellulosic biowastes have been used for oil spill removal, e.g., Ali et al reported the synthesis of oleophilic gels from n-butyl acrylate for oil spill cleanup. 11 Gum tragacanth, a natural polysaccharide, was grafted with acrylic acid and methylmethacrylate by Saruchi et al for oil spill remediation. 12 He et al proposed the utilization of aerogels derived from carboxymethylated chitosan which showed remarkable oil adsorption capacities along with excellent regeneration ability.…”
Section: Introductionmentioning
confidence: 99%